2022
DOI: 10.1177/10283153221121394
|View full text |Cite
|
Sign up to set email alerts
|

Universities Need a Social License to Operate and Grow: Reflecting on the University-Community Engagement of two Transnational Universities

Abstract: Transnational higher education is big business. However, it is unclear what transnational universities must do to behave in a responsible way or to gain a social licence to operate. Examining the University of Nottingham Ningbo China (UNNC) and Xi'an Jiaotong-Liverpool University (XJTLU), we discuss what universities could do to gain approval from host communities. They have to meet home and host country regulations, and the expectations of local communities and other stakeholders. Consideration of their socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Marginalisation and anomie appear to be widespread, particularly among early career faculty (Brotherhood & Patterson, 2023; Morley et al., 2019; Sakurai & Mason, 2022, 2023). Researchers have found that international faculty are often motivated to remain in Japan (Chen & Chen, 2023), but struggle to effectively negotiate their broader integration (Chen, 2022a) with Japanese language ability being a mediating factor (Chen, 2022b). Prior research has shown that language ability is a defining factor when it comes to international academics work roles and opportunities for advancement (Huang, 2018a, 2018b).…”
Section: Diversifying Academic Mobility and The Growing Importance Of...mentioning
confidence: 99%
See 1 more Smart Citation
“…Marginalisation and anomie appear to be widespread, particularly among early career faculty (Brotherhood & Patterson, 2023; Morley et al., 2019; Sakurai & Mason, 2022, 2023). Researchers have found that international faculty are often motivated to remain in Japan (Chen & Chen, 2023), but struggle to effectively negotiate their broader integration (Chen, 2022a) with Japanese language ability being a mediating factor (Chen, 2022b). Prior research has shown that language ability is a defining factor when it comes to international academics work roles and opportunities for advancement (Huang, 2018a, 2018b).…”
Section: Diversifying Academic Mobility and The Growing Importance Of...mentioning
confidence: 99%
“…Recently, attention has turned to the ongoing challenge of retaining international faculty (Kim et al., 2022; Luczaj, 2022; Pustelnikovaite, 2021; Spitzer & Zhou, 2018). First among these challenges is a reported lack of integration into their host institutions (Brotherhood & Patterson, 2023; Chen & Chen, 2023; Hoang, 2020) which is attributed to several factors, including marginalisation on campus (Chen & Zhu, 2022; Munene, 2014), power imbalances between local and international faculty (Van Der Wende, 2015) and, particularly in non‐Anglophone contexts, linguistic challenges (Gress & Shin, 2020; Huang, 2018b). Evidence also suggests that, while efforts are made to attract international faculty, institutional support for faculty integration is rare and ad hoc (Jepsen et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…That said, a growing sector‐wide interest in demonstrating corporate social responsibility and cohering with triple‐bottom‐line reporting, concepts that are certainly privileged by international accreditation entities, might suggest a growing degree of isomorphism when it comes to stated public and private value propositions. In short, it could well be that both public and private tertiary entities might feel the need to make broadly similar public value propositions in order to maintain their social licence to operate, and gain the support of their respective communities (Chen & Vanclay, 2023).…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…Private universities have increased remarkably over the years (Kinyanjui & Juma, 2014). At present, there are 30 chartered public universities with five constituent colleges, 18 chartered private universities with five private constituent colleges, 13 universities with a letter of interim authority, and one private institution (CUE, 2020). It is clear that university sector will continue to grow, but few will survive in the future (Manyeki et al, 2018).…”
Section: Introductionmentioning
confidence: 99%